Unpacking the relationships between positive feeding practices and children's eating behaviours: The moderating role of child temperament. (1st April 2020) - Holley, Clare E.; Haycraft, Emma; Farrow, Claire
Abstract: Evidence suggests that children's eating behaviours are influenced by the feeding practices which parents employ. Furthermore, parents may alter the feeding practices they use according to their child's temperament. However, there is a paucity of literature on how children's temperament moderates the relationship between parents' use of feeding practices and children's eating behaviours. One hundred and eleven mothers of 2 to 4-year-old children completed questionnaire measures of their feeding practices along with their child's eating behaviours and temperament. Two-tailed Spearman's correlations revealed that mothers' use of a range of positive (health promoting) feeding practices was associated with greater enjoyment of food and lower food fussiness among children. Moderation analyses found that relationships between mothers involving their children in food choice and preparation and children's eating behaviours were moderated by children's temperament. Involvement in food choice and preparation was no longer associated with higher enjoyment of food and lower fussiness for children who were either highly emotional or low in sociability. These findings suggest that while many previously identified positive feeding practices may be associated with more healthy eating for all children, some may be less helpful or less achievable with children who have particular temperamental traits. Future research should seek to develop interventions to promote healthy eating which are tailored towards children's individual characteristics.